2022
DOI: 10.1101/2022.08.25.505358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive effects of thalamostriatal degeneration are ameliorated by normalizing striatal cholinergic activity

Abstract: The loss of neurons in parafascicular thalamus (Pf) and of their inputs to dorsomedial striatum (DMS) are associated with Lewy body disease (LBD) and Parkinsons disease dementia (PDD) and have been linked to the effects of neuroinflammation. In rats, these inputs regulate the function of striatal cholinergic interneurons (CINs) that are necessary for the flexible encoding of the action-outcome (AO) associations for goal-directed action. We found that these inputs modify the encoding, not retrieval, of new AO a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…5E-G). This is consistent with a recent study that showed that reversal learning increased the burst firing of DMS CINs [40].…”
Section: Resultssupporting
confidence: 93%
“…5E-G). This is consistent with a recent study that showed that reversal learning increased the burst firing of DMS CINs [40].…”
Section: Resultssupporting
confidence: 93%
“…Activation of thalamostriatal system has been shown to alleviate deficits in motor functions in PD model mice through striatal cholinergic interneurons 64,65 . In addition, blocking neuroinflammation in the Pf rescues cognitive impairment in PD model rats 66 . Thus, the CM/Pf complex may be a potential, effective target for therapeutic strategies for the symptoms of PD.…”
Section: Discussionmentioning
confidence: 99%